Temperature and precipitation at migratory grounds influence demographic trends of an Arctic‐breeding bird. (29th July 2020) - Doyle, Susan; Cabot, David; Walsh, Alyn; Inger, Richard; Bearhop, Stuart; McMahon, Barry J.
Abstract: Anthropogenic climate disruption, including temperature and precipitation regime shifts, has been linked to animal population declines since the mid‐20th century. However, some species, such as Arctic‐breeding geese, have thrived during this period. An increased understanding of how climate disruption might link to demographic rates in thriving species is an important perspective in quantifying the impact of anthropogenic climate disruption on the global state of nature. The Greenland barnacle goose ( Branta leucopsis ) population has increased tenfold in abundance since the mid‐20th century. A concurrent weather regime shift towards warmer, wetter conditions occurred throughout its range in Greenland (breeding), Ireland and Scotland (wintering) and Iceland (spring and autumn staging). The aim of this study was to determine the relationship between weather and demographic rates of Greenland barnacle geese to discern the role of climate shifts in the population trend. We quantified the relationship between temperature and precipitation and Greenland barnacle goose survival and productivity over a 50 year period from 1968 to 2018. We detected significant positive relationships between warmer, wetter conditions on the Icelandic spring staging grounds and survival. We also detected contrasting relationships between warmer, wetter conditions during autumn staging and survival and productivity, with warm, dry conditions being the most favourable for productivity. Survival increased in the latter part of the study period, supporting the possibility that spring weather regime shifts contributed to the increasing population trend. This may be related to improved forage resources, as warming air temperatures have been shown to improve survival rates in several other Arctic and northern terrestrial herbivorous species through indirect bottom‐up effects on forage availability. Abstract : Our study shows that survival in an Arctic‐breeding migrant bird, the Greenland barnacle goose Branta leucopsis, was positively associated with warmer, wetter conditions during spring staging over the past 50 years. Survival rates increased, while a concurrent regime shift towards warmer, wetter conditions occurred, supporting the view that weather regime shifts contributed in part to the increasing population trend observed since the mid‐20th century. Greenland barnacle geese are one of a number of herbivorous birds and terrestrial mammals with thriving population trends, and the indirect effect of climate disruption on forage resources is likely a key factor explaining this pattern.